2019
DOI: 10.1021/jacs.8b13055
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Addition of Cu–Carbenes to Acetylenes to Form Chiral Allenes

Abstract: Terminal alkynes have become one of the most versatile building blocks for C–C bond construction in the past few decades, and they are usually considered to convert to acetylides before further transformations. In this study, a novel direct nucleophilic addition mode for Cu­(I)-catalyzed cross-coupling of terminal alkynes and N-tosylhydrazones to synthesize chiral allenes is proposed, and it was investigated by density functional theory with the M11-L density functional. Three different reaction pathways were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 87 publications
1
29
0
Order By: Relevance
“…In our computational study, several different mechanistic scenarios were taken into account (Figure 5). 1 The Cu(I)catalyzed deprotonation of phenylacetylene could occur through transition state TS-10 with an activation free energy of 16.7 kcal/mol, reversibly generating copper acetylide intermediate 23. However, the followed carbenation step through the denitrogenation transition state TS-11 has an activation free energy of 40.8 kcal/mol, which indicates that this mechanism is less likely.…”
Section: Intermolecular Nucleophilic Addition To Metal Carbenementioning
confidence: 97%
See 2 more Smart Citations
“…In our computational study, several different mechanistic scenarios were taken into account (Figure 5). 1 The Cu(I)catalyzed deprotonation of phenylacetylene could occur through transition state TS-10 with an activation free energy of 16.7 kcal/mol, reversibly generating copper acetylide intermediate 23. However, the followed carbenation step through the denitrogenation transition state TS-11 has an activation free energy of 40.8 kcal/mol, which indicates that this mechanism is less likely.…”
Section: Intermolecular Nucleophilic Addition To Metal Carbenementioning
confidence: 97%
“…The electrostatic potential (ESP) and the frontier molecular orbitals (FMOs) of Cu-carbene intermediate 26 were analyzed to investigate the reactivity of this metal carbene. 1 The ESP map (Figure 6a) showed that carbene carbon C1 exhibits electropositive character. Meanwhile, the FMO analyses (Figure 6b) demonstrated that the LUMO of Cu-carbene 26 is mainly located at the p orbital of carbene carbon C1.…”
Section: Intermolecular Nucleophilic Addition To Metal Carbenementioning
confidence: 99%
See 1 more Smart Citation
“…The generated propargyl copper species would undergo a regioselective protonation to deliver the corresponding allene products (Scheme a). Recently, DFT calculations have suggested that a nucleo­philic attack of the alkyne to the copper carbene species followed by deprotonation of the generated vinyl cation is involved in the reaction mechanism, rather than the carbene migratory insertion process …”
Section: Olefination Of Ketones Aldehydes and Beyondmentioning
confidence: 99%
“…Recently, DFT calculations have suggested that a nucleophilic attack of the alkyne to the copper carbene species followed by deprotonation of the generated vinyl cation is involved in the reaction mechanism, rather than the carbene migratory insertion process. 75 Following this work, the substrate scope is then substantially expanded for the synthesis of allenes with various substitution patterns. Simple copper iodide is an efficient catalyst to catalyze the coupling of aldehyde derived N-tosylhydrazones with terminal alkynes under ligand-free conditions, providing 1,3disubstituted allenes in good yields (Scheme 15b).…”
Section: ■ Introductionmentioning
confidence: 99%